2020
DOI: 10.1097/ico.0000000000002501
|View full text |Cite
|
Sign up to set email alerts
|

Do Patients With Keratoconus Have Minimal Disease Knowledge?

Abstract: Purpose: To assess whether Swiss adult citizens diagnosed with keratoconus have the minimal knowledge that a corneal specialist would expect they should have.Methods: Experts defined the "minimal keratoconus knowledge" (MKK) with respect to definition, risk factors, symptoms, and possible treatment options of keratoconus. A survey was performed in 167 patients with keratoconus [mean age 38.8 years (SD 13.9), 77.7% male] in 5 specialized institutions. Of each participant, salient clinical characteristics, highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(41 citation statements)
references
References 11 publications
1
39
1
Order By: Relevance
“…We did not identify clinical features corelated with sex or age, however, the sex and age could potentially influence study results regarding the life habits. The absence of differences in clinical parameters between adult and adolescent patients indicates a rapid progression in the latter [57][58][59], pointing to the importance of increasing patient awareness [60] as well as early diagnosis due to substantial risk of progression. Generally, we focused on the regular patients, who best represent the overall patient population of the clinic.…”
Section: Plos Onementioning
confidence: 99%
“…We did not identify clinical features corelated with sex or age, however, the sex and age could potentially influence study results regarding the life habits. The absence of differences in clinical parameters between adult and adolescent patients indicates a rapid progression in the latter [57][58][59], pointing to the importance of increasing patient awareness [60] as well as early diagnosis due to substantial risk of progression. Generally, we focused on the regular patients, who best represent the overall patient population of the clinic.…”
Section: Plos Onementioning
confidence: 99%
“…In a previous study [13] assessing MKK in patients, a questionnaire was developed on the basis of a literature review and discussions held by a focus group of four corneal specialists and two contact lens-fitting optometrists. They defined the minimal knowledge an average keratoconus patient should have in relation to definition, risks and triggers, symptoms and treatment options of the disease.…”
Section: Questionnaire Developmentmentioning
confidence: 99%
“…They were instructed to restrict these to the most common set of characteristics that should be known by every keratoconus patient, excluding uncommon factors or unusual presentations of symptoms. In telephone interviews among ophthalmologists, we employed the same questionnaire than the one used to assess MKK in patients [13]. Although ophthalmologists arguably know more about the condition than patients, we refrained from expanding the questionnaire in order to ensure uniform assessment of patients and physicians.…”
Section: Questionnaire Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“… 15 A recent Swiss study of patients with keratoconus identified dramatically little knowledge about the typical signs, risk factors, and treatment options for keratoconus, and patients with a university degree showed only a moderately higher knowledge level. 16 Similarly, in this study, keratoconus literacy was low, with few parents reporting satisfactory understanding of keratoconus currently or at the time of diagnosis. Parents from socioeconomically marginalized backgrounds (ie, limited English proficiency, lower income, lower educational attainment, and unreliable transportation) endorsed poorer keratoconus literacy than parents from more privileged backgrounds.…”
Section: Discussionmentioning
confidence: 52%